Analysis of Retrofit Building Behavior with Base Isolation System Using Nonlinear Time History Analysis - Septiarsilia, Yanisfa; Tavio, Tavio; Raka, I Gusti Putu (IPTEK Journal of Proceedings Series, 2017)
Now,  procedures of design for the earthquake resistance of buildings and non-building structures SNI 1726: 2012 has been approved the procedures for seismic design for buildings SNI 1726-2002.  SNI 1726: 2012 refers to the development  of  modern seismic regulations are due to changes in tectonic plates located on the active track on the path of circum-Pacific and the Indian track - the Himalayas. With the enactment of the new  SNI earthquake,  namely SNI 1726: 2012, then all existing buildings and designed with old  SNI earthquake, that  is SNI - 1726-2002 should be evaluated against for the new regulations. Handling scheme for existing buildings should be made to determine and improve safety. Analysis and solutions are required to improve the safety of buildings. Retrofitting Seismic Isolation is one of  the effective and practical methode to increase safety of buildings against earthquakes, because  this methode can reduce the earthquake acceleration response. Retrofitting seismic isolation can not only improve the safety and functionality seismic, but also to maintain the original design. Without the need to demolish and rebuild the building, the building will remain intact. So that historic buildings and cultural heritage can still be preserved. The concept of base isolation is to decouple the upper structure from its foundation and inserting isolator which has a small horizontal stiffness. This techniques can reducing the seismic impact from the soil vibration which could be from seismic motion. This study will compare the ratio building safety for old structural design that uses SNI-1726-2002 (old) vs SNI 1726: 2012 (new). The results shows that retrofitting seismic isolation building have better performance in terms of ductility demand, natural period, and lower internal forces due to earthquake.